On the Domination of Transmission Approach and the Lack of Transaction – Parents in Municipal Primary Schools - Lulek, Barbara (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The scientific purpose of the study is to present results of researches devoted to relations between parents and teachers in municipal primary schools, in categories of a wider description of mutual connections of the aforementioned entities. The article consists of three main elements. The first one refers to the source literature and based on it outlines the surface for own researches. The second one refers to the presentation of methodological assumptions of the conducted research procedure. The third one includes an analysis of the collected research material. The presented research material allows to notice a peculiar bipolarity in relations between parents and teachers in municipal primary schools, covering transmission and transaction social relations, characterized by subjectification or objectification of parents by teachers or other school employees. In the municipal primary schools which participated in the research, parents indicate dominant objectification, based on information transmission from the teacher towards the parents, lacking a dialogue and deeper transactions with teachers of their own children, as the basic element of interpersonal relationships. Parents inform about a discrepancy between the horizon of their expectations and the surface of experiences, which facilitates the popularization of the transmission perspective, illustrating objectifications between teachers and parents.
Keywords: parents; education; parents subjectification; transaction; transmission